Integrasi Sistem Pesawat Udara Tanpa Awak dan Akal Imitasi untuk Pengawasan Kepabeanan dan Cukai - Edwin Iskandar Dinazar (JURNAL PERSPEKTIF BEA DAN CUKAI, 2025)
To enhance surveillance capability in coastal and land border areas, Directorate General of Customs and Excise (DGCE) has recently acquired locally-manufactured Remotely Piloted Aircraft Systems (RPAS). However, factors like the large area-of-interest to cover, limited personnel and assets, and post-flight data analysis hindered the optimization of the RPAS. On the other hand, the Ministry of Finance (MoF) in general has initiated Artificial Intelligence (AI) usage in strategic scenario planning through the establishment of MoF AI Community of Practices (CoP) in early 2025. The early stage of adoption of both technologies within MoF and DGCE present an opportunity for integration and future development. Various journal and industry practices had shown that the integration of AI into RPAS operation—including for surveillance operation—is highly feasible. This research aims to examine how RPAS operation for DGCE surveillance mission could be further enhanced by the integration of AI. This research employs a mixed-method approach, combining internal surveys from RPAS pilots, practical insights from external sources, and literature review on how RPAS and AI integration in surveillance mission. The findings highlight the stages of RPAS operation with possible AI integration—preparation, in-flight, and post-flight data analysis—, technological readiness of AI suitable for each stage, and challenges for the implementation. These results suggest that practical AI integration into existing RPAS could transform underutilized surveillance assets into powerful enforcement tools.